Molecular phylogeny and morphology reveal a new Hymenochaete species (Hymenochaetaceae, Basidiomycota) from China - Li, Yunchao; Chen, Minglan; Xiao, Wenyuan; Zhang, Junzhong; Zhao, Changlin (Phytotaxa, 2024)
Wood-inhabiting fungi play an essential role in forest ecosystems as an important group of decomposers, which are found in living trees, dead standing trees, decorticated trunks, fallen branches, as well as manufactured wood. A new wood-inhabiting fungus Hymenochaete sinensis, belonging to the family Hymenochaetaceae, is described and illustrated based on the morphological characteristics and molecular data. Hymenochaete sinensis sp. nov. is characterized by annual, resupinate basidiomata with aurantium to coconut brown to brownish black hymenial surface, a monomitic hyphal system having the simple-septate with distinctly thick-walled generative hyphae, and ellipsoid to broadly ellipsoid basidiospores measuring as 4–5 × 2.5–3.5 µm. The phylogenetic analyses based on ITS+nLSU rDNA sequences confirmed that the new species belongs to the genus Hymenochaete. The ITS phylogenetic tree revealed that the new taxon is closely related to species of Hymenochaete longispora and H. quercicola.